Description of the Level of Dental and Oral Health Knowledge among Parents of Child Patients Who Visited BLUD UPTD Banjar 1 Community Health Center September 29 - October 6 2023 - Viola Febi Kurniawan; Nathania Carissa Christabel; Oei, Tirza Cintya Sanjaya; Marvella Fidelia (SONDE (Sound of Dentistry), 2023)
Dental health knowledge is the understanding of all aspects of dental health care, including how to brush your teeth properly, a good diet for teeth, and regular dental checkups. Parents are responsible for their children's dental health, and therefore should have good knowledge of dental health. If parents' knowledge and understanding of dental health is not supportive, then children's dental health care behavior will become less supportive.The purpose of this study is to determine the level of dental health knowledge among parents of children who visited the BLUD UPTD Puskesmas Banjar 1 on September 29 to October 6, 2023. This study used a descriptive analytic research design using a questionnaire with 15 questions. The data from this study were then processed and categorized as good (51%), sufficient (46%), or insufficient (3%). The conclusion of this study is that the level of dental health knowledge among parents of children who visited the BLUD UPTD Puskesmas Banjar 1 on September 29 to October 6, 2023 is classified as good. Keywords : Knowledge, Dental health, Parents